2014
DOI: 10.1002/bmc.3121
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of dronedarone in rat using a newly developed high‐performance liquid chromatographic assay method

Abstract: A sensitive and selective high-performance liquid chromatographic method for the determination of dronedarone in rat plasma was developed. Dronedarone was extracted using one-step liquid-liquid extraction. The separation of dronedarone was accomplished using a C18 analytical column. The mobile phase was composed of a combination of monobasic potassium phosphate and acetonitrile. The UV detection was at 254 nm for ethopropazine, the internal standard, and after its elution, changed to 290 nm for dronedarone det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…During method development and optimization of the extraction procedure, several different organic solutions and mixtures were tested, including acetonitrile and ethyl acetate (Jardan, Gabr, & Brocks, ; Kumar et al, ; Wang, Deng, Chen, Guo, & Zhong, ). The result showed that ethyl acetate had higher recovery, lower background and acceptable matrix effects.…”
Section: Resultsmentioning
confidence: 99%
“…During method development and optimization of the extraction procedure, several different organic solutions and mixtures were tested, including acetonitrile and ethyl acetate (Jardan, Gabr, & Brocks, ; Kumar et al, ; Wang, Deng, Chen, Guo, & Zhong, ). The result showed that ethyl acetate had higher recovery, lower background and acceptable matrix effects.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that a mixture of acetonitrile and distilled water (60:40, v/v) was the optimized mobile phase with better resolution, lower background noise, more symmetrical peaks and short retention time for analytes. During method development and optimization of the extraction procedure, several different organic solutions and mixtures were tested, including acetonitrile and ethyl acetate ( Jardan et al, 2014;Kumar et al, 2013). The result showed that ethyl acetate had higher recovery with lower background.…”
Section: Methods Development and Optimizationmentioning
confidence: 98%
“…Dronedarone HCl tablets (Multaq) was from Sanofi‐Aventis (Laval, PQ, Canada). Chemicals and sources used for drug analysis were as reported previously . Isoflurane USP was purchased from Halocarbon Products Corporation (River Edge, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The measurements of dronedarone was accomplished using HPLC. The validated lower limit of quantitation was 25 ng/mL for dronedarone, based on 0.1 mL of plasma .…”
Section: Methodsmentioning
confidence: 99%